2010
DOI: 10.1002/cncr.25657
|View full text |Cite
|
Sign up to set email alerts
|

Trends, patterns, and outcomes in the management of malignant colonic polyps in the general population of the United States

Abstract: BACKGROUND: Colonoscopic screening has increased detection of malignant colonic polyps (MPs). The goal of this study was to analyze trends and patterns in the surgical treatment of MPs and to assess outcomes as measured by lymph node retrieval and patient survival. METHODS: The Surveillance, Epidemiology, and End Results (SEER) registry was queried to identify 19,743 patients with MPs from 1988 to 2003. RESULTS: The majority of MPs were present in the sigmoid and descending colon (54%), and 38% were tubular, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 27 publications
(29 reference statements)
5
46
2
2
Order By: Relevance
“…With regard to the site of malignant polyps in our series, our result (56%) of left colon localisation is in keeping with data published by Wasif et al [9], whereas we had a slightly higher right colon localisation than that reported in the meta-analysis by Hassan et al [10].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…With regard to the site of malignant polyps in our series, our result (56%) of left colon localisation is in keeping with data published by Wasif et al [9], whereas we had a slightly higher right colon localisation than that reported in the meta-analysis by Hassan et al [10].…”
Section: Discussionsupporting
confidence: 93%
“…They described -in a general population setting -a median removal of just one node. This type of behaviour has prognostic consequences, as patients with fewer resected lymphnodes have been shown to have a survival disadvantage [9].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Wasif et al showed that polyps larger than 3 cm could be completely excised only in 67-75% of cases, thus questioning the endoscopic approach (5). In our present study, a large polyp size is the commonest cause for laparoscopic removal of colorectal polyps after a suspected malignancy.…”
Section: Discussioncontrasting
confidence: 48%
“…There are several methods to remove polyps by using either endoscopic, surgical, or combined methods (4). Patients who have known adenomas and refuse removal develop colon cancer at the rate of 4% after 5 years and 14% after 10 years, which is higher than that of the general population (5). Endoscopic removal of polyps has been shown to arrest subsequent development of carcinoma (6).…”
Section: Introductionmentioning
confidence: 99%
“…An analysis from a large database in the USA demonstrated a median harvest of one node in patients who underwent colon resection for malignant polyps [127]. Gill, in the analysis of data of the Northern Colorectal Cancer Audit Group in UK on management of malignant colorectal polyp reported that the median lymph node yield was 9.0, reflecting current practice over a range of experience and hospital size from district general hospitals to tertiary referral centres [74].…”
Section: Lymph Node Harvestingmentioning
confidence: 98%